ASEAN Countries Strategies in Developing Tourism Post Covid-19 Vaccination - Salam, Usmar (Sekolah Vokasi, Universitas Gadjah Mada, 2023)
This research aims to implement vaccination in order to encourage tourism growth in ASEAN. The relationship between vaccination and tourism growth, especially in ASEAN countries, is very important. This research focuses on Indonesia, Singapore, Malayasia and Vietnam which have reopened their borders to stimulate the tourism sector. This research uses qualitative research methods to look specifically at each country's policies regarding vaccination. The result of this research is that ASEAN governments are slowly easing it to save their tourism industry. At the regional level, the ASEAN Tourism Ministers' Meeting resulted in cooperation in operating the ASEAN Tourism Crisis Communication Team (ATCCT). From this meeting, it is hoped that in the future ASEAN countries will collaborate and have an integrated policy in the tourism sector, especially after the pandemic, considering that ASEAN is very dependent on tourism as one of the main sources of income.